Scale-dependent response of the urban heat island to the European heatwave of 2018 - Shreevastava, Anamika; Prasanth, Sai; Ramamurthy, Prathap; Rao, P Suresh C (Environmental research letters, 2021)
Extreme heat continues to be a pressing challenge of the changing climate. The impacts of extreme heat manifest on two different spatio-temporal scales: (1) episodic continent-wide heatwaves (HWs) and (2) the city-scale urban heat island (UHI). As HWs are becoming more frequent, longer, and severe, they pose serious implications of increased public health risks at a city scale, and have adverse impacts on agricultural and terrestrial/aquatic ecosystems on the regional scale. Here we offer a fresh perspective of the HW as a forcing that invokes dynamic, heterogeneous, scale-dependent responses evident in inter and intra-urban heat islets. A numerical simulation of the 2018 European HW including the surface and air temperature-based UHIs of six urban agglomerations, with a high-resolution focus on Paris, serves as our case study. We find that the mean nighttime UHI intensities are reduced for inland cities but increased for coastal cities. Our examination of the heat islets reveals two major findings: (i) the HW homogenizes the intra-urban surface temperatures during the daytime (reduces variance), (ii) the HW impacts are most significant on the scale of large, spatially discontiguous extreme heat islets during nighttime. These results underscore the need to move beyond the prevalent HW-mean UHI intensity characterization and toward intra-urban heat islet analyses that aid targeted mitigation.